A Managerial Decision Making Capability Framework For Adopting Technology Innovation Within Construction SMEs : Analysis and Results (Sains Humanika, 2016)
The slow adoption of new technology within construction SMEs is influenced by the capability of managers in making decisions. Therefore, this paper aims to report the development of a conceptual framework related to managersâ€™ decision making capability in adopting technological innovation; specifically referring to Building Information Modelling (BIM). The primary data collection involves semi-structured interview, while the multiple-case (holistic) design was used for developing the managerial decision making capability framework.. The development of the framework was analysed using comparative analysis (cross-case ) of thirteen (13) top managers within the construction SMEs organisations. Comparisons were made between existing theories and new concepts raised by top managers. The findings revealed thatÂ  regardless of various views obtained from top managers, the adoption of BIM software has been influenced by managerial non-behavioural and behavioural capability, that have been categorised into five (5) main themes.
Keywords: Decision making capability; top managers; construction; technology innovation adoption; conceptual framework